Long-term treatment with Perampanel of Chinese patients with focal-onset seizures, especially in sleep-related epilepsy: a prospective real-world observational study - Xu, Ye; Wang, Qinyue; Zhang, Yufei; Chen, Yuncan; Xu, Lan; Zhu, Guoxing; Ma, Chunlai; Wu, Xunyi (Frontiers in Neurology, 2024)
Background There is currently a lack of studies examining the long-term therapeutic effectiveness of the third-generation anti-sezure medication, perampanel (PER), for focal-onset seizures (FOS), particularly in Chinese patients with sleep-related epilepsy (SRE). Additionally, the appropriate dosage, plasma concentration, and the relationship between dose and plasma concentration of PER in Chinese patients are still uncertain. Methods A prospective, single-center, 24-month observational study was conducted in patients diagnosed with FOS, with a focus on patients with SRE. Changes in seizure frequency from baseline, adverse events, and retention rates were analyzed at 12 and 24 months following the start of the treatment. Tolerability was evaluated based on adverse events and discontinuation profiles. PER plasma concentrations were used to assess dose-concentration-response relationships. Results A total of 175 patients were included (median age: 25 years; range: 4–72 years; 53. 1% males and 46.9% females), with the SRE population accounting for 49. 1% (n = 86). The patients diagnosed with SRE showed considerably higher response rates than those who did not have this diagnosis (p = 0.025, odds ratio = 3.8). Additionally, the SRE group adhered better to PER treatment (r = 0.0009). Patients with a shorter duration of epilepsy (median: 3 years; range:2–7 years) demonstrated a more favorable therapeutic response to PER (p = 0.032). Throughout the administration of maintenance doses, among the entire FOS population, the concentration of PER (C0) ranged between 101.5 and 917.4 ng/mL (median, 232.0 ng/mL), and the mean plasma concentration of PER in the responders was 292.8 ng/mL. We revealed a linear relationship between PER dose and plasma concentration, regardless of whether PER was used as monotherapy or add-on therapy. The retention rates were 77.7% and 65. 1% at 12 and 24 months, respectively. Drug-related adverse events occurred in 45.0% of the patients and were mostly manageable. Conclusion PER effectively reduced seizure frequency in Chinese patients with FOS, particularly in those with SRE, over a 24-month period. The treatment was well-tolerated and had a clear linear dose-plasma concentration relationship.